Remote surveillance of enclosed and open architectures using unmanned vehicle with advanced security - Khetan, Ayushman; Sarkar, Abhirup; Sabunwala, Hussain; Gupta, Eshan; Ramachandran, Harikrishnan; Shahane, Priti (Institute of Advanced Engineering and Science, 2024)
Monitoring behavior, numerous actions, or any such information is considered as surveillance and is done for information gathering, influencing, managing, or directing purposes. Citizens employ surveillance to safeguard their communities. Governments do this for the purposes of intelligence collection, including espionage, crime prevention, the defense of a method, a person, a group, or an item; or the investigation of criminal activity. Using an internet of things (IoT) rover, the area will be secured with better secrecy and efficiency instead of humans, will provide an additional safety step. In this paper, there is a discussion about an IoT rover for remote surveillance based around a Raspberry Pi microprocessor which will be able to monitor a closed/open space. This rover will allow safer survey operations and would help to reduce the risks involved with it.